1984
DOI: 10.1128/jcm.20.5.927-932.1984
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of lysis-centrifugation with lysis-filtration and a conventional unvented bottle for blood cultures

Abstract: Evaluation of a commercially available lysis-centrifugation blood culture system (Isolator, DuPont Co., Wilmington, Del.) and a lysis-filtration blood culture system for 3,111 cultures showed that both methods had comparable recoveries (73 and 68%, respectively) of significant aerobic and facultatively anaerobic isolates. The unvented conventional blood culture bottle had a recovery rate of 59%. Although the lysis-centrifugation and lysis-filtration systems had comparable recoveries of pathogens, the lysis-cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

1985
1985
2007
2007

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…The observed incidences as well as magnitudes of bacteremia were higher than those described previously, confirming the high sensitivity of the combination of lysis-filtration and brain heart infusion agar (6). Asymptomatic bacteremia (7,16) and a high frequency of contamination have been reported in connection with blood culture systems based on lysis of blood (5,6), and therefore, preoperative blood samples must also be obtained in order to estimate the true postoperative bacteremia. In the present study, we decreased the frequency of contamination from 7%, as reported previously (6), to 0% in 300 blood samples by changing the laboratory procedures from daily microscopic examination to one single examination after 10 days.…”
Section: Discussionmentioning
confidence: 99%
“…The observed incidences as well as magnitudes of bacteremia were higher than those described previously, confirming the high sensitivity of the combination of lysis-filtration and brain heart infusion agar (6). Asymptomatic bacteremia (7,16) and a high frequency of contamination have been reported in connection with blood culture systems based on lysis of blood (5,6), and therefore, preoperative blood samples must also be obtained in order to estimate the true postoperative bacteremia. In the present study, we decreased the frequency of contamination from 7%, as reported previously (6), to 0% in 300 blood samples by changing the laboratory procedures from daily microscopic examination to one single examination after 10 days.…”
Section: Discussionmentioning
confidence: 99%
“…IS previously has been shown to be inferior to radiometric BACTEC bottles for recovery of all streptococci combined and for viridans group streptococci (5). Although the IS tube is an acceptable method for detecting bacteria, this system has been reported to have a higher contamination rate relative to that of BACTEC bottles and to be inferior to other systems for recovery of certain bacteria (particularly streptococci, pseudomonads, and anaerobic bacteria) (5,7,14,15,17).…”
Section: Discussionmentioning
confidence: 99%
“…The findings for the WBL-F and FH-CF blood culture techniques differ from those of other existing reports. Previous works on the subject (1,10,13) showed that the centrifugation filtration and lysis filtration techniques (6,34,35) were able to detect bacteria quicker than conventional blood culture techniques. Nevertheless, these techniques are cumbersome not only because of the excessive handling of the sample but also because of the potential clogging of the filtration system with blood debris (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…Once the product was filtered, the side of the filter that had been in contact with the bacteria was placed on trypticase soy agar to plate the bacteria. As soon as bacterial growth was detected, identification tests were carried out (6,9,23,(28)(29)(30)35). Eighteen blood cultures for B. abortus and 18 for S. typhi were carried out.…”
Section: Methodsmentioning
confidence: 99%